2022
DOI: 10.3390/nano12244409
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials Based on Honey and Propolis for Wound Healing—A Mini-Review

Abstract: Wound healing is a public health concern worldwide, particularly in chronic wounds due to delayed healing and susceptibility to bacterial infection. Nanomaterials are widely used in wound healing treatments due to their unique properties associated with their size and very large surface-area-to-volume ratio compared to the same material in bulk. The properties of nanomaterials can be expanded and improved upon with the addition of honey and propolis, due to the presence of bioactive molecules such as polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 106 publications
0
1
0
Order By: Relevance
“…Recently, a systematic review and meta-analysis of more than 40 published studies found strong evidence that propolis is effective in the treatment of skin wounds, including difficult-to-heal ulcers found in patients with diabetes; in fact, propolis was shown to promote a higher percentage of healing than the interventions classically employed [25]. Another interesting aspect is that a large number of in vivo studies have combined propolis with other substances, such as honey, and different biomaterials (nanoparticles, nanofibrous, biocelullose membrane, hydrogel) to achieve additive or synergistic effects in the skin regeneration process [25,[57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review and meta-analysis of more than 40 published studies found strong evidence that propolis is effective in the treatment of skin wounds, including difficult-to-heal ulcers found in patients with diabetes; in fact, propolis was shown to promote a higher percentage of healing than the interventions classically employed [25]. Another interesting aspect is that a large number of in vivo studies have combined propolis with other substances, such as honey, and different biomaterials (nanoparticles, nanofibrous, biocelullose membrane, hydrogel) to achieve additive or synergistic effects in the skin regeneration process [25,[57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm refers to microorganism communities in wounds, which can hinder the healing process due to increased bacterial resistance. However, honey comes to the rescue by also being effective against biofilm bacteria [ 215 ]. When curcumin was released from electrospun nanofibers made of chitosan and polylactic acid, it showed no harmful effects on L-929 fibroblast cells and increased antioxidant activity in vitro.…”
Section: In-vitro Studiesmentioning
confidence: 99%
“…From fibers electrospun with honey to the healing of wounds: A review of abnormal collagen and the synthesis of normal collagen with its maturation (28) and promotes the emergence of blood vessels (29)(30)(31)(32).…”
Section: Honey As a Therapeutic Agent In Wound Healingmentioning
confidence: 99%